ANALISIS KETIMPANGAN PEMBANGUNAN EKONOMI ANTAR KAPANEWON SE-KABUPATEN BANTUL TAHUN 2013 DAN 2018 - Desembriarto, Dionysius (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Every region in Indonesia, including Bantul Regency, DI Yogyakarta, carries out development, especially in the economic sector to advance the region and improve the welfare of its people. Economic development in Bantul Regency shows increasing performance with increasing economic capacity as measured by Gross Regional Domestic Product (GRDP) and GRDP per capita from year to year, although in 2020 there was a decline in economic performance due to the impact of the Covid-19 pandemic. Although there is an increase in welfare, there are still problems in the economic development of Bantul Regency, namely the occurrence of inequality in welfare achievements between Kapanewon. The results of the analysis show that the level of inequality in economic development between Kapanewon in 2018 increased compared to 2013. The increasing in the inequality was caused by the different of the per capita income increasing achieved by each Kapanewon. Affirmative intervention efforts must be carried out by the government to further intensify economic activities in less prosperous regions, especially in areas with low per capita income both in 2013 and 2018